2008
DOI: 10.1515/ijamh.2008.20.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, hypertension, and mental health evaluation in adolescents: A comprehensive approach

Abstract: The global epidemic of childhood and adolescent obesity in developing and developed countries has become a major public health concern. Given the relation between obesity and hypertension as documented in several landmark studies, it is no surprise that as the prevalence of obesity has increased in the pediatric population, the rates of hypertension have also increased substantially. Hypertension is one of the most important risk factors for cardiovascular diseases and stroke; therefore, evaluation and initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 50 publications
0
8
0
7
Order By: Relevance
“…No entanto, ainda existem controvérsias acerca do impacto da obesidade sobre a saúde mental dos indivíduos 2,3 . Alguns estudos sugerem que a obesidade pode levar a problemas de saúde mental 4 , enquanto outros mostram que adolescentes que apresentam problemas de saúde mental são mais propensos à obesidade 5 . Para estabelecer essa relação, são necessários estudos prospectivos, os quais ainda são escassos 3,6 .…”
Section: Introductionunclassified
“…No entanto, ainda existem controvérsias acerca do impacto da obesidade sobre a saúde mental dos indivíduos 2,3 . Alguns estudos sugerem que a obesidade pode levar a problemas de saúde mental 4 , enquanto outros mostram que adolescentes que apresentam problemas de saúde mental são mais propensos à obesidade 5 . Para estabelecer essa relação, são necessários estudos prospectivos, os quais ainda são escassos 3,6 .…”
Section: Introductionunclassified
“…There is evidence that hypertension in children and adolescents can lead to adult hypertension. 2,3 Hypertension is known as a risk factor for coronary artery disease in adults, and the presence of hypertension in children and adolescents may contribute to the early development of coronary artery disease. Previous reports have shown that early development of atherosclerosis does exist in children and adolescents and may be associated with childhood hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…По данным Всемирной организации здравоохранения, за по-следнее десятилетие XX века распространенность ожирения в мире в среднем увеличилась на 50 %. В Узбекистане среди населения частота ожирения со-ставляет 24,1 % [4].…”
Section: актуальностьunclassified
“…В результате проведенных европейскими учеными исследований было выяснено, что при повышении ин-декса массы тела (ИМТ) более 29 кг/м 2 возможность за-беременеть снижается на 4 % по сравнению с теми жен-щинами, чей ИМТ находится в пределах 21-29 кг/м 2 [4]. У пациенток, которые страдают выраженным ожирени-ем (ИМТ составляет 35-40 кг/м 2 ), вероятность забереме-неть без дополнительного медицинского вмешательства снижается на 7 %.…”
Section: актуальностьunclassified
See 1 more Smart Citation